Prediction, learning, and games - Cesa-Bianchi, Nicolò, 1963- (Cambridge University Press, 2006)
The central theme here is a model of prediction using expert advice, a general framework within which many related problems can be cast and discussed, including repeated game playing, adaptive data compression, sequential investment in the stock market, and sequential pattern analysis.